Design and Manufacturing Audio Bioharmonic Technology with Manipulate Peak Frequencies for Crop Field: Refpo Rahman - Refpo Rahman Refpo Rahman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2021)
Applied physics can be involved and integrated with various fields of science. Sonic bloom technology by utilizing sound waves in fact can increase plant growth. This research is the development of the audio bioharmonic (ABH) device to create an efficient, practical, and easy-to-use for farmers. The design and manufacturing of an ABH device based on an Arduino UNO Atmega 328p with manipulated frequencies have been done. The original sound source of Garengpung (Dundubia Manifera) was manipulated around the range of 3000-5000 Hz and the frequency spectrum was calculated using Fast Fourier Transform (FFT) analysis. The results show that the peak frequencies obtained are 3241, 4167, and 4963 Hz as the sound sources of mp3 files. Furthermore, the ABH device was validated by comparing the results of the FFT analysis of the sound source of the mp3 files with the sound recording of the ABH device. As the result, the deviations of the peak frequency obtained are 259, 140, and 172 Hz. And the last, the sound pressure levels (SPL) of audio bioharmonic output at different frequencies are measured using a sound level meter in real-time for 30 minutes. All frequencies have stable SPL at 80-100 dB.